Air-trapping bulla in the azygoesophageal recess as a “sentinel bulla” causing secondary spontaneous pneumothorax: A case report - Shinya Ito (Respiratory Medicine Case Reports)
Successful surgical management of spontaneous pneumothorax usually depends on identifying the pleural fistula that is causing the air leak. However, identifying the exact location of the air leak preoperatively is typically impossible. A peculiar thin-walled bulla located in the azygoesophageal recess can cause pneumothorax in patients with chronic obstructive pulmonary disease (COPD). A 61-year-old man with a history of COPD presented with exertional dyspnea. Chest radiography revealed a right pneumothorax. Upon reviewing previous chest computed tomography images, we ascertained that the air-trapping bulla in the azygoesophageal recess had grown consistently over the previous 2 years. Persistent air leakage was observed after chest tube drainage. Video-assisted thoracoscopy revealed a thin-walled bulla with a fistula in the azygoesophageal recess. We encountered an expanding bulla in the azygoesophageal recess that eventually caused spontaneous pneumothorax. Definitive management guidelines for secondary spontaneous pneumothorax caused by azygoesophageal recess bullae with unique features remain elusive.